1994
DOI: 10.1289/ehp.94102s1213
|View full text |Cite
|
Sign up to set email alerts
|

Environmental genotoxicity: probing the underlying mechanisms.

Abstract: Environmental pollution is a complex issue because of the diversity of anthropogenic agents, both chemical and physical, that have been detected and catalogued. The consequences to biota from exposure to genotoxic agents present an additional problem because of the potential for these agents to produce adverse change at the cellular and organismal levels. Past studies in genetic toxicology at the Oak Ridge National Laboratory have focused on structural damage to the DNA of environmental species that may occur … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
1

Year Published

1994
1994
2016
2016

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 14 publications
1
27
0
1
Order By: Relevance
“…One of the potentially most productive approaches would be to: a) use biomarkers to identify individuals sensitive to exposure (29); b) determine the genotypes of these individuals at critical loci; c) determine the genotypes of tolerant individuals at these same loci; d) determine whether certain alleles at these loci conferred greater fitness and, ideally, why that was the case; and then e) determine the frequencies of genotypes at these loci in exposed and unexposed populations. This might be particularly easy to address at the microbial level.…”
Section: Goals and Challengesmentioning
confidence: 99%
“…One of the potentially most productive approaches would be to: a) use biomarkers to identify individuals sensitive to exposure (29); b) determine the genotypes of these individuals at critical loci; c) determine the genotypes of tolerant individuals at these same loci; d) determine whether certain alleles at these loci conferred greater fitness and, ideally, why that was the case; and then e) determine the frequencies of genotypes at these loci in exposed and unexposed populations. This might be particularly easy to address at the microbial level.…”
Section: Goals and Challengesmentioning
confidence: 99%
“…Besides, several studies have revealed that TWW often still contains mutagens (genotoxic substances) that can not only injure the integrity of the genome of organisms but also negatively affect the expression of DNA directly or indirectly (Shugart and Theodorakis, 1994;Filipic and Toman, 1996;Grisolia et al, 2005). This leads to an increase in different types of tumors and subsequently an alteration in the genetic variability of the exposed populations over time (Zhiyi and Haowen, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Emphasis has been given on the effective detection of mutations as it not only provides the basis for biomonitoring, but also serves to identify vulnerable stages in the life history of a species, the nature and dynamics of causal agents and associated phenotypic and population-level effects (Shugart and Theodorakis, 1994). Several genotoxic effects like, DNA adducts, DNA breakage, chromosomal aberrations and sister chromatid exchanges can be observed in organisms exposed to various pollutants (Venier et al, 1997;Das & John, 1999).…”
Section: Tools In the Study Of Genotoxicitymentioning
confidence: 99%